2014
DOI: 10.1002/jcb.24726
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐590 Promotes Cervical Cancer Cell Growth and Invasion by Targeting CHL1

Abstract: MicroRNAs (miRNAs) may function as oncogenes or tumor suppressors. Here, we identified that miR-590-5p was up-regulated in human cervical cancer. Over-expression of miR-590-5p promoted cervical cancer cell growth, cell cycle and invasion via Growth curve, Colony formation, FACS and Transwell assays in HeLa and C33A cell lines. Subsequently, CHL1 was identified as a potential miR-590-5p target by bioinformatics analysis. Moreover, we showed that CHL1 was negatively regulated by miR-590-5p at the posttranscripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 21 publications
6
61
0
1
Order By: Relevance
“…It has been reported that miR-590-5p is up-regulated in human cervical cancer. Cell growth, cell cycle and invasion are induced by the over-expression of miR-590-5p in HeLa and C33A cell lines (Chu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-590-5p is up-regulated in human cervical cancer. Cell growth, cell cycle and invasion are induced by the over-expression of miR-590-5p in HeLa and C33A cell lines (Chu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of miR-590 has been found in hepatocellular carcinoma [16] and cervical cancer [17]. However, the relationship between miR-590 and T-ALL has never been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion ability was investigated by transwell assay29. 200 μL HeLa cells (2 × 10 5 /mL in serum free RPMI-1640) transfected with nano-lipoplexes (PLP/PAAV 2 , FLP/PAAV 2 , PLP/PEDF and FLP/PEDF) were placed on the top chamber of each transwell (8 μm pore size, Corning, America) coated with 50 μL diluted Matrigel (volume ratio to RPMI-1640 serum-free was 1:3).…”
Section: Methodsmentioning
confidence: 99%